2013
DOI: 10.1155/2013/613064
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Copper Complexes: Molecular Structure, Properties, and Its Application to Solar Cells

Abstract: We present a theoretical investigation of copper complexes with potential applications as sensitizers for solar cells. The density functional theory (DFT) and time-dependent DFT were utilized, using the M06 hybrid meta-GGA functional with the LANL2DZ (D95V on first row) and DZVP basis sets. This level of calculation was used to find the optimized molecular structure, the absorption spectra, the molecular orbitals energies, and the chemical reactivity parameters that arise from conceptual DFT. Solvent effects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Additionally, three basis sets LANL2DZ for Ru, double-ζ, and 6-311+G­(2d,p) for C, N, S, O, and H elements ,,, were implemented. It has been reported that M06 has appropriate ability to study characteristics of organometallic compounds. ,,, The calculated HOMO–LUMO gap value from M06 functional shows a variation of less than 0.05 eV on average for neutral N719 derivatives. For dianionic derivatives, a variation of 0.06 eV (on average) was obtained when different basis sets were employed (for neutral and derivative complexes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, three basis sets LANL2DZ for Ru, double-ζ, and 6-311+G­(2d,p) for C, N, S, O, and H elements ,,, were implemented. It has been reported that M06 has appropriate ability to study characteristics of organometallic compounds. ,,, The calculated HOMO–LUMO gap value from M06 functional shows a variation of less than 0.05 eV on average for neutral N719 derivatives. For dianionic derivatives, a variation of 0.06 eV (on average) was obtained when different basis sets were employed (for neutral and derivative complexes).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds N719, N719-2, N719-7, and N719-8 are singlets, while the other molecules are doublets. The absorption spectra of derivatives (neutral and dianionic) have been computed with time-dependent density functional theory (TD-DFT) , using M06/LANL2DZ/6-311+G­(2d,p). Theoretically, the intensity of the band is expressed in terms of the oscillator strengths ( f ).…”
Section: Computational Detailsmentioning
confidence: 99%
“…The molecular structure and properties of ve Cu(I) complexes with the general formula [CuL 2 ] + (L ¼ bipyridine ligands) proposed as sensitizers in dye-sensitized solar cells have been studied by DFT methods employing the M06 HM-GGA density functional and the LANL2DZ and DZVP basis sets. 85 The characterization of the molecular systems included the calculation of geometric parameters, ultraviolet-visible spectra, electronic excited states, molecular orbitals, and chemical reactivity parameters.…”
Section: 2mentioning
confidence: 99%
“…For a complex to be used as a dye, the absorption spectra of the dye should have strong absorption peaks in the ultraviolet-visible (UV-Vis, ca. 350-750 nm) regions of the solar spectrum [20][21][22]. The experimental spectra of complexes 1-9 have a strong absorbance peak between 270-376 nm, with a lower energy LMCT in the 400-600 nm region.…”
Section: Application As Dye To Dsscmentioning
confidence: 98%